1996
DOI: 10.1007/bf00024054
|View full text |Cite
|
Sign up to set email alerts
|

The control of shoot tip necrosis in Pistacia vera L. in vitro

Abstract: The effect of increased concentrations of calcium (Ca) (3-24 mM) and boron (B) (100-800 PM) in the medium was studied on the occurrence of shoot tip necrosis (SIN) in cultures of Pistacia Vera L. STN was significantly reduced by application of Ca or B, however media with more than 200 PM boron had reduced shoot multiplication. Ca (12-24 mM) supplied as calcium chloride reduced STN without any adverse effect on shoot multiplication or elongation, whereas calcium acetate reduced elongation. It is concluded that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 26 publications
3
33
0
Order By: Relevance
“…The present study revealed that the calcium deficiency symptoms such as shoot tip necrosis (STN) and leaf drop could be prevented by increasing the calcium concentration in the media. This corresponds with the findings in Pistacia vera L., where STN was significantly reduced by increased application of calcium (Barghchi and Alderson 1996) and, in another study, a correlation between STN and low calcium content was found in shoots of Vitis vinifera L. (Thomas 2000). H. rosa-sinenesis L. explants exhibited a significant reduction in shoot number, when calcium concentration was increased.…”
Section: Effects Of Calcium and Bap Levelsupporting
confidence: 88%
See 2 more Smart Citations
“…The present study revealed that the calcium deficiency symptoms such as shoot tip necrosis (STN) and leaf drop could be prevented by increasing the calcium concentration in the media. This corresponds with the findings in Pistacia vera L., where STN was significantly reduced by increased application of calcium (Barghchi and Alderson 1996) and, in another study, a correlation between STN and low calcium content was found in shoots of Vitis vinifera L. (Thomas 2000). H. rosa-sinenesis L. explants exhibited a significant reduction in shoot number, when calcium concentration was increased.…”
Section: Effects Of Calcium and Bap Levelsupporting
confidence: 88%
“…The higher shoot number per explant at lower calcium level was therefore seen as a stress symptom, and the shoots at low calcium level were of poor quality. A decrease in the shoot multiplication rate with increased calcium concentration has also been reported in P. vera L. (Barghchi and Alderson 1996) and Eucalyptus tereticornis Smith (Sharma and Ramamurthy 2000). Another example of stress symptoms at lower calcium level was the low leaf area per shoot due to poor leaf development and leaf drop.…”
Section: Effects Of Calcium and Bap Levelmentioning
confidence: 86%
See 1 more Smart Citation
“…The composition of the media used for establishment of aseptic cultures is important. Several limitations such as low shoot proliferation in forest trees, excessive phenolic exudation (Linington 1991), basal callusing (Marks and Simpson 1994), vitrification (Monsalede et al 1995), and shoot tip necrosis (Bargchi and Alderson 1996) are pronounced in tree tissue culture. Further, difficulty in rooting (Noiton et al 1992;Harada and Murai 1996) has also had a negative effect on micropropagation of woody forest tree species in vitro.…”
Section: Micropropagation Of Tree Without Intervening Callus Phasementioning
confidence: 99%
“…browning of buds and youngest leaves, one would automatically assume the cause to be nutrient deficiency. The symptoms of nutrient deficiency of less mobile minerals such as Ca and B (Raven 1977) often appear first in the meristematic regions and young leaves while symptoms of excessive presence of these minerals are observed in the older leaves (Barghchi and Alderson 1996). However, STN in vitro is the function of a complex set of factors.…”
Section: Introductionmentioning
confidence: 98%